Kopipasta / Nabil Pius ... [et al.] - Pius, Nabil; Saban, Amizal Shazrin; Ali Rahman, Mohd Azizul (2015)
Kopi Pasta is a Coffee Shop located in No. 20 Jalan Aru, Kota Kinabalu, Sabah 88100, Malaysia that allows the entire family to have their Coffee needs satisfied in one convenient location. Kopi Pasta serves all customers and try to satisfy their needs and wants. Kopi Pasta also sells pastry products. Kopi Pasta is able to serve the entire family in one quick, convenient visit. While there are many cafes like Kopi Pasta, Kopi Pasta will excel due to its attention to detail regarding customer service. Through unheralded customer attention, Kopi Pasta will slowly but surely gain market share as it services the entire family, creating long-term relationships. Lastly Kopi Pasta location will allow it to attract a lot of walk in traffic. People across Malaysia have decided to use our services when they want to fulfil their coffee needs, for example to have their unique taste of coffee or a delightful taste of pastry cake. Kopi Pasta has foreseen this opportunity to provide the finest and highest quality of coffee and pastry product to all people, despite their age or gender. This has shown that Kopi Pasta has the calibre to be one of the most successful cafe in Malaysia. We, Kopi Pasta, saw the opportunity that this business has the potential of success provided that it is handled efficiently. The people have always needed to have coffee in order to work long hours as well as a reward after a long day of work. Kopi Pasta sees this as a way to prosper in this market, by taking advantage of all these people's need.